Turīyamīmāṃsā : anekadurvādimataparāsanapurassaram, Śruti-Smrtītihāsa-Purāṇāni puraskrtya tāni pariṣkrtya ca turīyāśramamīmāṃsāsanaparā - Śāstrī, Rāmamiśra (SAMP early 20th-century Indian books project, 1901)
On the fundamental Vedic principles and their interpretation.